Pengaruh Intellectual Capital terhadap Nilai Perusahaan - Nanik Lestari; Rosi Candra Sapitri (Politeknik Negeri Batam, 2016)
This study aimed to analyze the effect of intellectual capital on firm value. Intellectual capital measured in this study with the Pulic model (1998). Firm Value measured by Tobin's Q Control variables used in the study is size, leverage, and growth. The population of this research are manufacturing companies listed in Indonesia Stock Exchange (BEI) 2010-2013. Samples were selected using purposive sampling method with sample 252 (firm – years). This study uses multiple regression analysis and descriptive statistics for the analysis of the data processed by the program eviews 8.0. The results of this study is intellectual capital (VAIC/value added intellectual coefficient) does not affect on firm value. The control variables such as size, leverage, and growth was also not significantly affect on firm value.